Effects of Intralabyrinthine Hemorrhage on the Cochlear Elements: A Human Temporal Bone Study. Issue 2 (February 2016) - Kaya, Serdar; Hizli, Ömer; Schachern, Patricia A.; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Hypothesis: To compare histopathologic findings in the cochlea of human temporal bones with versus without intralabyrinthine hemorrhage. Background: Hemorrhagic labyrinthitis can cause sensorineural damage, sudden hearing loss, and vertigo. Yet, to our knowledge, no studies have quantitatively described histopathologic effects of intralabyrinthine hemorrhage on the elements of the cochlea. Methods: We analyzed 46 human temporal bone samples from 23 patients with unilateral intralabyrinthine hemorrhage (23 samples from ears with intralabyrinthine hemorrhage and 23 samples from contralateral ears without). We noted the location of hemorrhage in the inner ear, the degree of endolymphatic hydrops, the number of spiral ganglion cells and hair cells, mean loss of fibrocytes in spiral ligament, and areas of the stria vascularis and spiral ligament. Results: Intralabyrinthine hemorrhage caused significant loss of outer hair cells in the lower basal ( p  = 0.001), upper basal ( p  = 0.005), and lower middle ( p  = 0.012) cochlear turns. The degree of endolymphatic hydrops was significantly different between the hemorrhagic and contralateral sides ( p  = 0.011). But we found no significant difference between the 2 sides in the number of inner hair cells, spiral ganglion cells, and fibrocytes, or in the areas of the stria vascularis and spiral ligament between the two groups ( p  > 0.05). Conclusion: These findings suggest that such patients could be good candidates for hearing aid or cochlear implant if they have profound sensorineural hearing loss.